Penerimaan Diri pada Ibu yang Memiliki Anak Berkebutuhan Khusus (Studi Kasus di Rumah Belajar Hamirah Kabupaten Bekasi) - Aulya Sholihatul Afiyyah; Budi Sarasati; Andreas Corsini Widya Nugraha (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
This research aims to aims to: 1) Knowing the meaning of self-acceptance in mothers who have children with special needs, 2) Describe the characteristics of self-acceptance in mothers who have children with special needs, 3) Understand the process of self-acceptance in mothers who have children with special needs. The method used in this research is a qualitative method with a case study approach. This study involved one subject and two informants. The subject of this research is a mother who has a child with special needs. Data collection methods in this study used interviews, observation, and documentation. This research is expected to reveal the process of self-acceptance experienced by mothers who have children with special needs. Based on the results of the study, the researcher obtained findings in the form of the subject's self-acceptance process from before knowing the diagnosis to after knowing the diagnosis. In the process of achieving s elf-acceptance as a mother of a child with special needs, the subject is also faced with various life struggles that are not easy for him to get through. The struggle carried out by the subject to the support he got was a trigger for the subject to reach the stage of acceptance of himself as a mother of a child with special needs.